(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article analyzes the assessment of education quality in general secondary schools based on international experiences. The effectiveness of competency-based assessment and pedagogical monitoring approaches used in Finland, Singapore, and South Korea is highlighted. The study concludes that adapting international practices to the local context plays an important role in improving overall educational outcomes.